Evaluasi Kinerja Keuangan Badan Layanan Umum Daerah, Rumah Sakit Umum Daerah Lubuk Sikaping Tahun 2016 sd 2021: - - Rini, Marwan Saputra; Muharja, Fajri (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
The purpose of this study is to analyze the financial performance of the BLUD RSUD Lubuk Attitude from 2016 to 2022, identify the determinants of financial performance, and formulate what policies are needed to encourage the financial performance of the BLUD RSUD for the future. The sample used in this study is officials/employees who are considered experts and understand the financial problems of the BLUD RSUD. The sampling technique used in this study was purposive sampling technique with a total sample of 9 people. The analytical technique used in this study uses financial ratio analysis, compliance analysis, and the AHP method, to solve the problems encountered by formulating several priority policies and strategies with the Analytichal Herarchy Process method which will be useful and as consideration for the hospital management in . The results showed that the 2016 BLUD RSUD financial performance criteria were good or A, 2017 had A or good criteria, 2018 had moderate or BB criteria, 2019 had moderate or BBB criteria, 2020 had good criteria or A, and 2021 had good criteria or A. In addition, the main priority policies formulated to encourage financial performance are the aspect of human resources with a priority weight (57.09%), the second aspect of service with a weight (18,76%), the third aspect of regulation (13.98%), and the last aspect local government support (10.17%).